Plasmodium falciparum Clearance Is Pitting-Dependent With Artemisinin-Based Drugs but Pitting-Independent With Atovaquone-Proguanil or Mefloquine. (16th March 2019) - Wojnarski, Mariusz; Mouri, Oussama; Chambrion, Charlotte; Roussel, Camille; Chartrel, Nathalie; Smith, Bryan; Smith, Philip; Thellier, Marc; Buffet, Pierre; Ndour, Papa Alioune
Abstract: Pitting, the removal of dead parasites from their host erythrocyte, has been studied in patients with severe malaria treated parenterally with quinine or artesunate, and was recently shown to contribute to delayed hemolysis, a frequent adverse event of artesunate. We quantified pitting in 81 travelers treated with oral antimalarial therapy. Pitting rate was high (55.8%) with artemisinin-based combinations, but <10% with the nonartemisinin drugs quinine, mefloquine, and atovaquone-proguanil. This may, in part, explain the slower parasite clearance in patients treated with antimalarial drugs lacking an artemisinin component, as well as the absence of posttreatment hemolysis with these drugs. Abstract : We quantify the appearance of circulating erythrocytes from which parasites have been expelled, following therapy of malaria with different medications. The findings likely explain the slower parasite clearance and absence of delayed anemia with therapies devoid of an artemisinin component.